DEVELOPMENT OF LEARNING MODULES ON THE BASIC MATERIALS OF AUTOCAD 3D DRAWING FOR CLASS XII TPM AT SMKN 1 DRIYOREJO - Apria Nur Eka Falah; Aditya Pramono (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Negeri Semarang, 2023)
This study aims to develop teaching materials in the form of learning modules for valid 3D coordinate system material and basic 3D drawing and get positive responses from students. Development of learning modules using 4D models. The subject of this study was students of class XII Mechanical Engineering at Driyorejo State Vocational School 1 in semester 2 of the 2022/2023 academic year. Based on the results of the development, it was obtained that the module validity from the material aspect was 0.9 which was categorized as high validity, and for the media aspect the validity was obtained was 0.8 which was categorized as high validity. In the Dissemination stage of the learning module, improvements are made according to validator input, and trials are also carried out on students to find out the response to the learning module being developed. Of the students' responses, around 91% gave a positive response.